The discovery of uterine carcinosarcoma through a sister mary joseph's nodule: A case report - Wissal Jaafar; Medemagh Malak; Chiba Yasmine; Sadek Gueddana; Nahed Khalifa; Mechaal Mourali (Radiology Case Reports)
The Sister Mary Joseph nodule is a rare sign of advanced malignancy, including uterine carcinosarcoma. A 55-year-old woman presented with a necrotic, bleeding 4 cm umbilical mass. Biopsy confirmed uterine carcinosarcoma (FIGO stage IVB), and she was scheduled for chemotherapy and radiotherapy. This case underscores the need to recognize umbilical nodules as potential markers of widespread cancer.